Construction of tumor microenvironment and redox responsive nanocarrier-mediated cisplatin co-delivery system for effective chemotherapy to pancreatic cancer. Issue 2 (1st June 2022) - Jia, Zhou-Yan; Zhou, Hao; Hou, Li-Shuang; Kou, Fang; Zhang, Tang-Rui; Wang, Bao-Long; Wang, Wei; Zhou, Si-Yuan; Zhang, Bang-Le
Abstract: Pancreatic cancer is a malignant tumor with a high mortality rate. The rich stroma in tumor tissue is a major barrier to drug penetration and tumor killing. Cisplatin and cisplatin-based nano-delivery systems are widely used as chemotherapeutic agents. However, the side effects and the inability of permeating tumor tissue in depth have limited their application in the clinic. Hyaluronan is an important component of the extracellular matrix in the tumor tissue and has the potential to be targeted for tumor stroma degradation. Therefore, a nanocarrier-mediated cisplatin co-delivery system BPEI-SS-Pt/HAase@CaP consisting of hyaluronidase (HAase) and polymer-cisplatin conjugate BPEI-SS-Pt through disulfide bonding to branched polyethyleneimine (BPEI) was constructed. In the construction of the co-delivery system of BPEI-SS-Pt and HAase, amorphous calcium phosphate is introduced to obtain the tumor microenvironment responsive release of HAase. The particle size of optimized BPEI-SS-Pt/HAase@CaP nano-complexes is 143 ± 14 nm. In the tumor microenvironment, BPEI-SS-Pt/HAase@CaP nano-complexes were able to release HAase to degrade the hyaluronan in the tumor stroma. The results of histochemical and fluorescent labeling showed that hyaluronan was degraded in vivo by BPEI-SS-Pt/HAase@CaP and the nanocarrier-mediated BPEI-SS-Pt can be easily across the loosened stroma and penetrated the tumor tissue more deeply compared with BPEI-SS-Pt without loading HAase. When they were uptaken into tumor cells and responded to high glutathione in the intracellular environment to release cisplatin, more effective chemotherapy to pancreatic cancer was obtained. Compared with the free cisplatin or BPEI-SS-Pt group, BPEI-SS-Pt/HAase@CaP nano-complexes achieved the best antitumor effect in vivo, promising the future clinic use of cisplatin for effective chemotherapy to pancreatic cancer.